Remittance behavior among Salvadoran and Filipino Immigrants in Los Angeles - Menjivar, C.; Da Vanzo, Julie; Greenwell, L.; Valdez, R. B.
tbls.
pp. 97-126
Keywords: Inmigración; Estados Unidos de America; Los Angeles; Remesas; Filipinas; El Salvador